Structural Analysis of Aspiration Catheters and Procedural Outcomes: An Analysis of the SVIN Registry - Jaydevsinh N. Dolia; Mahmoud H. Mohammaden; Mohamed A. Tarek; Mateus Damiani; Jonathan A. Grossberg; Aqueel Pabaney; Michael Frankel; Dinesh V. Jillella; Ameer E. Hassan; Wondwossen G. Tekle; Alexandros Georgiadis; Hamzah Saei; et al. (Stroke: Vascular and Interventional Neurology)
Background Rapid expansion of mechanical thrombectomy and swift manufacturing development has translated into significant evolution of large‐bore catheter technology. The objective of this study was to evaluate the association among diverse structural components of large‐bore aspiration catheters on procedural performance. Methods Retrospective analysis of a prospectively maintained mechanical thrombectomy consortium (SVIN [Society of Vascular Interventional Neurology] Registry) treated with stand‐alone contact aspiration for the first pass in the middle cerebral artery M1 or intracranial internal carotid artery occlusions from 2012 to 2021. Catheters were stratified on the basis of construction materials, tip technology, catheter sizing, and catheter lining. Factors associated with first‐pass effect (first‐pass eTICI 2c–3 reperfusion) as well as speed of clot engagement were analyzed. Results We identified 983 patients with proximal occlusion and aspiration as the first‐pass technique. First‐pass effect was observed in 34% and associated with age (odds ratio [OR], 1.02 [95% CI, 1.01–1.03]), cardioembolic stroke pathogenesis (OR, 1.69 [95% CI, 1.77–2.41]), middle cerebral artery M1 (OR, 2.74 [95% CI, 1.09–1.87]), nongeneral anesthesia (OR, 0.55 [95% CI, 0.39–0.767]), as well as with 0.070‐inch (OR, 2.04 95% CI, 1.01–3.78]), and 0.088‐inch (OR, 3.90 [95% CI, 1.58–9.61]) distal catheter inner diameter in the adjusted analysis. Mean time from arterial access to clot contact was 17 minutes, with faster times observed in younger patients (OR, 0.99 [95% CI, 0.98–0.996]) as well as with the use of aspiration catheters with shorter length of distal outer hydrophilic coating (18–30 cm) on multivariable regression (OR, 0.30 [95% CI, 0.11–0.82]). Conclusion Larger aspiration catheter distal inner diameter was associated with higher rates of first‐pass effect. Aspiration catheter construction components were found to influence times from arterial access to clot contact.